Building and Applying Quantitative Adverse Outcome Pathway Models for Chemical Hazard and Risk Assessment. (8th August 2019) - Perkins, Edward J.; Ashauer, Roman; Burgoon, Lyle; Conolly, Rory; Landesmann, Brigitte; Mackay, Cameron; Murphy, Cheryl A.; Pollesch, Nathan; Wheeler, James R.; Zupanic, Anze; Scholz, Stefan
Abstract: An important goal in toxicology is the development of new ways to increase the speed, accuracy, and applicability of chemical hazard and risk assessment approaches. A promising route is the integration of in vitro assays with biological pathway information. We examined how the adverse outcome pathway (AOP) framework can be used to develop pathway‐based quantitative models useful for regulatory chemical safety assessment. By using AOPs as initial conceptual models and the AOP knowledge base as a source of data on key event relationships, different methods can be applied to develop computational quantitative AOP models (qAOPs) relevant for decision making. A qAOP model may not necessarily have the same structure as the AOP it is based on. Useful AOP modeling methods range from statistical, Bayesian networks, regression, and ordinary differential equations to individual‐based models and should be chosen according to the questions being asked and the data available. We discuss the need for toxicokinetic models to provide linkages between exposure and qAOPs, to extrapolate from in vitro to in vivo, and to extrapolate across species. Finally, we identify best practices for modeling and model building and the necessity for transparent and comprehensive documentation to gain confidence in the use of qAOP models and ultimately their use in regulatory applications. Environ Toxicol Chem 2019;38:1850–1865. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC. Abstract : Quantitative adverse outcome pathway (AOP) model development.